STUDY OF THE INTERACTION OF POTASSIUM CHLORIDE WITH AMMONIUM SULFATE SOLUTION - Absattorov, Diyorbek (Techscience uz - Topical Issues of Technical Sciences, 2025)
This comprehensive study investigates the thermodynamic and kinetic aspects of potassium chloride interaction with ammonium sulfate solutions under controlled laboratory conditions. The research focuses on optimizing the conversion process for potassium sulfate production through double salt formation methodology. Experimental investigations were conducted using flotation potassium chloride obtained from the Tyubegatan mineral deposit in Uzbekistan and high-purity ammonium sulfate solutions. The study systematically examines the influence of solid-to-liquid ratios, reaction temperature, and processing duration on the chemical composition of both solid and liquid phases during the conversion process. Results demonstrate that optimal double salt formation occurs at solid-to-liquid ratios of 1:(1.7-2.0), maintaining reaction temperature at 25°C with 60-minute processing duration. Under these conditions, the resulting double salt К2SO4•(NH4)2SO4 exhibits superior quality with K₂O content reaching 50.90-51.20% and minimal impurity levels. The findings provide valuable insights for industrial implementation of environmentally sustainable potassium sulfate production technologies in mineral processing applications